Synthesis and photothermal/photodynamic antimicrobial activities of phthalocyanines tetra-substituted by morpholinyl moieties. (April 2023) - Fan, Ping-Ping; Li, Shun-Li; Zheng, Bi-Yuan; Zheng, Bing-De; Lv, Li-Li; Ke, Mei-Rong; Huang, Jian-Dong
Abstract: A series of ɑ-tetra-substituted phthalocyanines (M = 2H, Cu, Co, Ni) with morpholinyl moieties and their corresponding quaternized derivatives have been synthesized. The spectroscopic and photosensitizing properties, photothermal effects, aggregation trend, and partition coefficients of these phthalocyanines are evaluated. Besides, we appraised their photothermal and photodynamic activities against C. albicans and E. coli under near-infrared (NIR) light irradiation (680 nm). The results show that cationic phthalocyanines are more efficacies in killing bacteria and fungi than their neutral analogues. For copper (II) phthalocyanine 4b and metal-free phthalocyanine 7b, their photodynamic activities play a key role in antimicrobial treatment, while for other phthalocyanines, their photothermal effects play a major role. Moreover, metal-free phthalocyanine 7b exhibits an ideal synergistic photothermal/photodynamic antimicrobial activity and shows the highest photocytotoxicity among all the compounds. The IC90 values of 7b towards C. albicans and E. coli are as low as 1.12 μM and 0.47 μM, respectively, while others have IC90 values ranging from 3.31 μM to 50 μM, implying that 7b would be a good candidate for future antimicrobial applications. Graphical abstract: Image 1 Highlights: A series of phthalocyanines substituted with morpholinyl moieties have been synthetized. The structure-activity relationships of these compounds have been discussed. The cellular uptake and photocytotoxicity increased after quaternization. The cationic 7b shows the highest photocytotoxicity against C. albicans and E. coli.